A leadership primer for new librarians : tools for helping today's early-career librarians to become tomorrow's library leaders - Byke, Suzanne (Chandos information professional series., 2009)
This book provides strategies and practical tips for leadership development in the field of librarianship. With the increase of both new graduates entering the field and upcoming retirements, there is a foreseeable gap in library leadership. Many early-career librarians will move into roles they are not ready for and others will find themselves having to lead without being in traditional leadership roles. This book offers suggestions for librarians facing these challenging new circumstances. The book shows how to create leadership opportunities when none appear to be present, how to take charge of your own professional development, and how to become an effective follower as well as an effective leader. The book helps the reader to recognize and take advantage of the leadership opportunities set before them. Defines effective leadership and followership for early-career librariansIncludes stories of common experiences turned into leadership development opportunitiesIdentifies and addresses the need for leadership development in early-career information professionals.